Scenarios of Human Resources Management Development as a Reaction to Changes in the External Surrounding (Economic and Political Thought, 2013)
Human Resources Management (HRM) is essentially predeterminedby the external determinants. The aim of the article is to focus on thoseprocesses whose substance and influence power create the utmost challengesfor the HRM in the nearest and further future, and then show thealternative scenarios for dealing with problems they generate. Therefore,the attention is focused on the aging processes of the (Polish) society (as aneffect of demographic changes), dematerialization of work (as an effect oftechnological changes) and financialization (as an effect of market changes).Two scenarios of HRM development are presented: the “economizing”one, which is a continuation of the reactions to global processes that are inprogress (here: talent management, work flexibility, management by results)and the “humanistic” one, built of alternative approaches (here: diversitymanagement, flexicurity, corporate social responsibility).